2019
DOI: 10.1088/1742-6596/1380/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface diffusion length on steady-state persistence probabilities

Abstract: The dependence of the steady-state persistence probabilities (Ps) and exponents (θs) on surface diffusion length (l) for four discrete growth models is investigated. The persistence exponents which describe the decay of the persistence probabilities, the probabilities of the average of all initial height (h 0), are increased as l is increased for all models. The results of one-dimensional Family ((1+1)-Family) and Das Sarma-Tamborenea ((1+1)-DT) models with kinetically rough film surface show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For all discrete growth models, P ± S (t)∝ t -θ ± S , where θ ± S is the persistence exponent which indicates how long the fluctuations last. In up-down symmetric models, θ + S = θ -S [9,[12][13]18]; while in asymmetric models, θ + S ≠ θ -S [9][10]14,18].…”
Section: The Persistence Probabilities and Exponents In The Steady-statementioning
confidence: 98%
See 2 more Smart Citations
“…For all discrete growth models, P ± S (t)∝ t -θ ± S , where θ ± S is the persistence exponent which indicates how long the fluctuations last. In up-down symmetric models, θ + S = θ -S [9,[12][13]18]; while in asymmetric models, θ + S ≠ θ -S [9][10]14,18].…”
Section: The Persistence Probabilities and Exponents In The Steady-statementioning
confidence: 98%
“…Another method to analyse this asymmetry is the study of persistence probabilities, which is the topic of this work. Persistence probabilities of height fluctuations [9][10][12][13][14][15][16][17][18] are probabilities that indicate how well the height fluctuations can maintain their initial properties. There are two types of persistence probabilities, which are the positive and the negative one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chanphana & Chatraphorn (Chanphana and Chatraphorn, 2019a) demonstrated that the diffusion length (l) affects the value of the persistence exponents. In our work, l can be varied by adjusting the growth parameters i.e., the substrate temperature, and the deposition rate.…”
Section: P Smentioning
confidence: 99%